Advances in PNP-ligated rare-earth-metal complexes: Reactivity and catalytic performances - Hongfan Hu; Rongqing Ma; Chenxi Cui; Guoliang Mao; Shixuan Xin (Polyolefins Journal, 2023)
Due to the large ionic radius and high electro-positivity nature, rare earth metal complexes are difficult to stabilize and undergo pathways like ligand redistribution and intramolecular C-H activation. To solve such problems and retain reactive versatility, rare earth complexes supported by a variety of tridentate PNP pincer ligands have been explored. Such complexes can serve as perfect precursors for preparing ultra-active rare earth species containing two metal-carbon bands, let alone Ln=N and Ln=P multiple bonds. In addition, the combined stability and activity of the cation rare earth mediates made them the best catalysts for the polymerization of olefins and other non-polar hydrocarbon monomers, especially conjugated dienes. The practical utilization of rare earth metal catalysts for new materials production have also extensively explored by experts from the academic and industries.